4-Methylumbelliferone Attenuates Macrophage Invasion and Myocardial Remodeling in Pressure-Overloaded Mouse Hearts. Issue 6 (22nd March 2021) - Hackert, Katarzyna; Homann, Susanne; Mir, Shakila; Beran, Arne; Gorreßen, Simone; Funk, Florian; Fischer, Jens W.; Grandoch, Maria; Schmitt, Joachim P.
Abstract : Supplemental Digital Content is available in the text. Abstract : Cardiac wall stress induces local and systemic inflammatory responses that are increasingly recognized as key modulators of extracellular matrix remodeling. Hyaluronic acid interacts with immune cells and mesenchymal cells thereby modulating profibrotic signals. Here we tested the hypothesis that 4-methylumbelliferone (4-MU), an inhibitor of hyaluronic acid synthesis, would attenuate inflammation and extracellular matrix remodeling of pressure-overloaded myocardium in C57BL/6J male mice fed with 4-MU and subjected to TAC (transverse aortic constriction) surgery. Flow cytometry of immune cells showed TAC-induced leukocytosis due to an increase of neutrophils and monocytes. 4-MU strongly attenuated both circulating and cardiac leukocyte numbers 3 days after TAC. In the hearts, 4-MU reduced the number of CCR2 − resident macrophages. At later time points, 4-MU also prevented the infiltration of heart tissue by bone marrow-derived circulating monocytes leading to reduced cardiac macrophage counts even 7 weeks after TAC. The long-term attenuation of macrophage-driven inflammation was associated with less myocardial fibrosis in 4-MU-treated compared with untreated mice. Unexpectedly, 4-MU also reduced the development of left ventricular hypertrophy and increased cardiac output after TAC without affecting blood pressure. The data demonstrate that 4-MU reduces both resident and invading cardiac macrophages and may be a promising agent to alleviate pressure-overload induced myocardial damage.